Small-scale maize farmers' perceptions and adaptations towards climate change in Makhuduthamaga Local Municipality, Sekhukhune District, Limpopo Province - Noko, Kabelo (My University, 2023)
The agricultural sector is a vital component of the South African economy. The industry has the ability to contribute to rural growth, eliminate poverty, improve food security, create jobs, and narrow income disparities. Climate change, on the other hand, poses a threat to South Africa's agricultural sector, water resources, food security, health, infrastructure, and ecosystem services and biodiversity as a result of rising temperatures and less rainfall. Climate change adaptation techniques such as changing or adjusting planting date, use of soil and water as conservation techniques have gained traction as an essential strategy alongside mitigation around the world, and are widely documented in a variety of sources and approaches (such as books, journal articles, reports etc.). Nonetheless, few studies have been conducted in South Africa to prove or analyse if these techniques will be implemented at the farm level, notably in Makhuduthamaga Local Municipality, Sekhukhune District, Limpopo Province. Furthermore, little or no research has been performed to determine whether the small-scale maize farmers from the area have perceived that climate is changing and they are will to adapt to those methods. As a result, this study was carried out to fill the aforementioned research information gap and to draw relevant policy implications to increase the welfare of small-scale maize farmers through the application of perceptions and adaptation towards climate change. The study's overarching goal was to analyse small-scale maize farmers' perceptions and adaptation towards climate change in Makhuduthamaga Local Municipality, Sekhukhune District, Limpopo Province. The study specifically addressed the following objectives: (i) Identify and describe small-scale maize farmer’s socio-economic characteristics in the study area; (ii) Assess the level of perceptions of small-scale maize farmers towards climate change in the study area; and (iii) Analyse the socio-economic factors influencing perceptions and adaptation of small-scale maize farmers towards climate change in the study area. A simple random sampling procedure was used to select 110 small-scale maize farmers from a sample frame of 238 based on probability proportional to sample size. The qualitative and quantitative cross-sectional data were collected through group observation and face-to-face interviews using structured questionnaires from Mid-December 2021 to Mid- February 2022. The empirical model that was employed to address the research objectives include; Heckman two stage equation model in chapter five. The data collected was analysed using IBM SPSS Version 27.0 and Microsoft excel 2016, respectively. To assess the perceptions of sampled small-scale maize farmers in the study area, the Likert-scale method of analysis was used. The majority of small-scale maize farmers interviewed 41 (37 %) strongly agreed that climate change is occurring, followed by those who were doubtful or uncertain 27 (25 %). Twenty four (22%) of the sample small-scale maize farmers agreed that climate change is occurring; however, 6% disagreed and 10% strongly disagreed. All the null hypotheses of the study are rejected because: the results from the descriptive statistics results shows that a large number of small-scale maize farmers strongly agreed and perceived or rather believed that climate has changed due to rainfall and temperature in the last 30 years. Lastly, the Heckman two stage equation model results revealed that age, educational level, farming experience, number of adult labourers, crop failure, credit access, access to extension services, farm size, perceived changes in temperature and rainfall and they all have a significant impact on the small-scale maize farmers’ perceptions and adaptation towards climate change. On the basis of empirical findings, it is proposed that the government, community members, and other stakeholders (such as NGOs, research institutions, municipalities, and so on) approach climate change adaptation as part of the local development plan. Investments in technologies such as irrigation, drought-resistant plants, and early maturing varieties; institution building; research; training; and promotion of small-scale farmers and animals such as cattle held to mitigate the effects of crop failure or low yields in extreme weather situations are some of the examples. This will also provide additional services required for adaptation, complicating the fulfilment of other development goals for long-term welfare.
Thesis (M.A. Agricultural Management (Agricultural Economics)) -- University of Limpopo, 2023
Keywords: Climate change; Adaptation to climate change; Small-scale maize farmers; Perceptions; Probability proportional to sample size; Climatic changes; Farmers -- South Africa; Farmers